Peningkatan Kemampuan Pemecahan Masalah Matematis Siswa SMP Melalui Pembelajaran Group Investigation Berbantuan Proyek - Wiwit Damayanti Lestari; Yaya Sukjaya Kusumah; Stanley Dewanto (Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of this study is to examine the differences in the improvement of students' mathematical problem-solving abilities in the classroom with investigation group learning assisted by projects and conventional learning classes. This study included quasi-experimental research with a non-equivalent control group research design. All mathematical problem-solving abilities of class VII students in one of the junior high Schools were the population in this study. Two classes were taken as samples, namely the experimental class applying the project-assisted investigation group and the control class that applied conventional learning. The question of mathematical problem-solving ability was used as an instrument in this study. Data on mathematical problem-solving ability from pretest and posttest then determined normalized gain average between two classes and analyzed using t-test. The results showed that the improvement of students' mathematical problem-solving abilities in the class applying project-assisted group learning was better than students in the class applying conventional learning, but the average increase in the two classes was in the moderate classification. So that project-assisted investigation group learning can be used as an alternative to improve the students' mathematical problem-solving skills in junior high school.